Surgical Treatment of Andersson’s Lesion in Ankylosing Spondylitis after Corrective Vertebrotomy in the Long Term (Clinical Observation) - V. V. Rerikh; E. V. Dubinin (Acta Biomedica Scientifica, 2021)
Using a clinical example, the authors set the goal of elucidating the result of a two-stage surgical treatment of Anderson’s lesion, carried out in the long-term period after a one-stage correction of flexion deformity of the  ankylosed spine without fixation.Results. The analysis of the results of treatment three years after decompression-corrective stabilizing surgery performed for Anderson’s lesion at the ThX–ThXI level, which developed 10 years after the correction of flexion deformity of the ankylosed spine by “open” vertebrotomy LIV–LV. No progression of Anderson’s lesion in all previously identified vertebral segments was noted. The existing neurological deficit regressed from ASIA C to ASIA E. Normalization of the SVA sagittal balance parameter was revealed, with preserved local kyphosis at the ThX–ThXI level of 15° (initial – 30°). The indicator ODI (Oswestry Disability Index), VAS and FIM (Functional Independence Measure) were, respectively, before surgery 67, 6 and 82, 3 years after surgery – 10, 0 and 126.Conclusion. In the presented case, the surgical correction of the deformity, carried out taking into account the parameters of the sagittal balance, with the stabilization of the ventral and dorsal columns, and decompression, made it possible to prevent the progression of Andersson’s lesion, achieve regression of neurological symptoms, and improve the patient’s quality of life.